Pengaruh Teman Sebaya dan Gaya Pacaran terhadap Perilaku Seks Pranikah pada Remaja Pria - Retnowati, Very (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2020)
Background: Premarital sex is a reproductive health problem that has a potential risk in adolescence. Sexual behavior in adolescents is influenced by various aspects, including peers, school environment, society, and socio-cultural aspects. Peers have an important role in social life and adolescent development. Friends who behave negatively are likely to have a negative influence on adolescents. This study aims to determine premarital sex behavior associated with the role of peers and adolescent dating style based on data analysis of the 2017 IDHS.Method: The population and sample are adolescents aged 14-24 years male and not married or living together. The dependent variable is young men who have had premarital sex and the independent variables are dating status, peer influence, and dating style. The design of this study is cross-sectional with logistic regression analysis model to see how much influence the dependent variable has on the independent variable.Results: The results showed an increased risk of premarital sex, including dating status (OR = 0.56; 95% CI 0.48-0.66; p = 0.000), friend motivation (OR = 2.92; 95% CI 2.48-3.43; p = 0.000), influence friends (OR = 1.44; 95% CI 1.12-1.85; p = 0.004), hand grip (OR = 0.45; 95% CI 0.22-0.93: p = 0.032), hugging (OR = 1.87; 95% CI 1.04-3.36: p = 0.035), kissing lips (OR = 3.54; 95% CI 2.41-5.20: p = 0.000), touching sensitive parts (OR = 21.90; 95% CI 16.42-29.20; p = 0.000). Peer motivation and peer influence of dating style such as kissing the lips and touching sensitive parts increase the risk of premarital sex.